1984
DOI: 10.1095/biolreprod31.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Mechanisms of Puberty in Heifers: Estradiol Negative Feedback Regulation of Luteinizing Hormone Secretion 1

Abstract: The hypothesis that luteinizing hormone (LH) secretion in prepubertal females is responsive to estradiol negative feedback and that decreased feedback occurs as puberty approaches was tested in heifers. In the first experiment, seven heifers were maintained prepubertal by dietary energy restriction until 508 days of age (Day 0). All heifers were placed on a high-energy diet on Day 0 at which time they received no additional treatment (CONT), were ovariectomized (OVX) or were ovariectomized and subcutaneously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
28

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 20 publications
5
81
0
28
Order By: Relevance
“…In addition, blood samples were collected on 10-day intervals during the development phase to estimate onset of puberty by determining the first pubertal increase in plasma progesterone concentrations. Heifers were considered pubertal once plasma progesterone concentrations were ⩾1.0 ng/ml, followed by a cyclic pattern of plasma progesterone < and ⩾1.0 ng/ml suggestive of normal estrous cycles (Day et al, 1984). Puberty attainment was declared at the first sampling that resulted in plasma progesterone ⩾1.0 ng/ml.…”
Section: Samplingmentioning
confidence: 99%
“…In addition, blood samples were collected on 10-day intervals during the development phase to estimate onset of puberty by determining the first pubertal increase in plasma progesterone concentrations. Heifers were considered pubertal once plasma progesterone concentrations were ⩾1.0 ng/ml, followed by a cyclic pattern of plasma progesterone < and ⩾1.0 ng/ml suggestive of normal estrous cycles (Day et al, 1984). Puberty attainment was declared at the first sampling that resulted in plasma progesterone ⩾1.0 ng/ml.…”
Section: Samplingmentioning
confidence: 99%
“…The onset of puberty in heifers is initiated by a decrease in oestradiol receptors in the hypothalamus and pituitary, ending the prepubertal negative feed-back and resulting in the first LH surge and ovulation (Day et al, 1984, Day et al, 1987. This shift occurs at a specific critical BW (as a proportion of adult BW) and critical age which varies amongst animals (Pence et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is generally accepted that this hypothesis may be applicable to farm species, appropri¬ ate experimental results are limited. Conflicting data have been recorded for the heifer; some workers have reported that episodic LH release increases gradually from birth to puberty (Schams et al, 1981;Day et al, 1984), while others have been unable to detect such changes (González-Padilla et al, 1975a;McLeod et al, 1984). The infrequent blood sampling regimen used in the study of Gonzalez-Padilla et al (1975a) was inadequate to identify changes in episodic patterns of gonadotrophin secretion, and the use of only limited periods of frequent sampling (Schams et 1981 ; Day étal, 1984) could lead to inaccurate estimations of LH episode frequency.…”
Section: Introductionmentioning
confidence: 99%